On the efficiency of the educational organization interactions with the parents of children with ASD - Mit6rofanova G.V (Moscow State University of Psychology and Education, 2018)
The article deals with the problem of psychological and pedagogical support of parents of children with autism spectrum disorders in the inclusive education environment. The results of the efficacy study of secondary schools specialists' interaction with parents are presented. Findings reveal that many parents are satisfied with the form of interaction with the educational organization, but at the same time they need additional consultations and various events that promote the establishment of partnerships with school specialists. Conclusion is made about the necessity for a specially organized psychological and educational support for parents of children with autism spectrum disorders studying in an inclusive school.